A Visible‐Light‐Driven Photocatalyst of NASICON Li2Ni2(MoO4)3 Nanoparticles. Issue 7 (19th April 2015) - Lu, Yuting; Li, Yuze; Huang, Yanlin; Chen, Cuili; Cai, Peiqing; Seo, Hyo Jin; Hintzen, H. T. J. M.
<x xml:space="preserve">Abstract</x> A visible‐light‐driven photocatalyst based on the well‐known cathode material of NASICON‐type Li2Ni2(MoO4)3 was prepared by a modified Pechini method. The sample was characterized by X‐ray diffraction, scanning electron microscope, transmission electron microscopy, and UV‐vis absorption spectrum. The average size of Li2Ni2(MoO4)3 particle is below 50 nm. NASICON nanoparticles Li2Ni2(MoO4)3 has an efficient absorption in the UV‐visible light wavelength region with a direct allowed electronic transition of 2.07 eV. The photocatalytic properties of Li2Ni2(MoO4)3 were evaluated by the photodegradation of methylene blue (MB). Li2Ni2(MoO4)3 has an efficient photocatalytic activity and could be a potential photocatalyst driven by visible‐light. The photocatalytic activity was discussed on the optical absorption and special hexagonal tunnel structure connected by optical active centers of MoO4 and NiO6 and its good conductivity.